Time in the Poem - Abdullrahman, Hussain O. (Humanities Journal of University of Zakho, 2014)
Time and Breath are a specified period of Existence. There is no meaning for existence without breath, and Literature, as a mirror of society, which carries Poetry and prose and it is a mean of showing the tiny seconds of life as well. It means that life is existence, and existence is equal to the time, therefore we can directly say that life equal to time. This time can be found in two different, external and internal, times in the structure of a poem. This research focuses on the internal time and its analysis by several examples in order to enable the reader to go further through inside the poet himself and to feel his feelings and emotions so as to understand the poem very well.